(untitled) (Journal of Telenursing (JOTING), 2022)
This study aimed to analyze the effect of chayote extract (Sechium edule) on malondialdehyde serum levels in white rats (Rattus norvegicus) fed a high-cholesterol diet and to prove the antioxidant content of chayote. The method used is experimental with a post-test-only control group design. This study used white rats, which were divided into five groups. The results of this study indicate that the administration of chayote extract at a dose of 0.25 g/kg BW and 0.5 g/kg BW can reduce the serum MDA concentration, although it is not statistically significant, while the administration of a chayote extract at a dose of 0.75 g/Kg BW can significantly reduce serum MDA levels in white rats induced by hypercholesterolemia. In conclusion, chayote extract at a dose of 0.75 g/kg BW can reduce blood MDA serum levels in white rats induced by hypercholesterolemia. Keywords: Chayote Extract, Hypercholesterolemia, Malondialdehyde